Diffusion coefficients of lithium chloride and potassium chloride in hydrogel membranes derived from acrylamide - Valente, A. J. M. (2002)
http://www.sciencedirect.com/science/article/B6TWW-4459YXC-3/1/786bf7fd6f201e0f9860c7daf36e864d